FEATURES OF ATTENTION DEVELOPMENT IN PRESCHOOL AGE CHILDREN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the theories and opinions of scientists about the emergence and development of attention in preschool children, that is, from 3 to 6 years old. First, we will consider what attention is and how important its role is in our lives.